Land Reclamation in Makassar City, Indonesia: The Case of Center Point of Indonesia (CPI) Reclamation - Inayah Mappatoba; Farda Nur Rahmani; Abdillah Abdillah; Thannaphat Khotsing (Government & Resilience, 2023)
The purpose of this research is to find out and analyze the connectedness of coastal land reclamation of the Center Point of Indonesia area with qualified development (SDG's) that is not in accordance with the concept of Open Government. In this study using the approach method used by the author is a normative juridical method, namely research on the principles of law, norms, and legal rules, and this research specification is an analytical descriptive research. The results of this study explain the inequality of the percentage of land area where 68% of profits run to the private sector, with the regulation of coastal and island zoning, this can be an opportunity for coastal communities to be free from environmental conflicts and natural resources. However, if observed from the draft ranperda RZWP3K Sulsel will only make way for miners to more freely exploit the sea with sand mines for reclamation in the city of Makassar, Indonesia. This research contributes to being an evaluation material for the Makassar City government in urban governance which needs to consider the social-ecological side of development which tends to be overlooked in development in urban areas.